Attenuation of Mycobacterium species through direct and macrophage mediated pathway by unsymmetrical diaryl urea - Velappan, Anand Babu (2016)
Tuberculosis is a major threat for mankind and the emergence of resistance strain of Mycobacterium tuberculosis (Mtb) against first line antibiotics makes it lethal for human civilization. In this study, we have synthesized different diaryl urea derivatives targeting the inhibition of mycolic acid biosynthesis. Among the 39 synthesized molecules, compounds 46, 57, 58 and 86 showed MIC values ≤ 10 μg/ml against H37Rv and mc26030 strains. The best molecule with a methyl at ortho position of the first aromatic ring and prenyl group at the meta position of the second aromatic ring showed the MIC value of 5.2 μg/ml and 1 μg/ml against H37Rv and mc26030 respectively, with mammalian cytotoxicity of 163.4 μg/ml. The effective compounds showed selective inhibitory effect on mycolic acid (epoxy mycolate) biosynthesis in14C-radiolabelled assay. At the same time these molecules also executed their potent immunomodulatory activity by up-regulation of IFN-γ and IL-12 and down-regulation of IL-10.